Should Phytase Be Given Release Values for Amino Acids and Energy in Diets for Growing Pigs? - M. R. Wensley; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; H. Calderon Cartagena (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 2,268 mixed gender pigs (PIC; 337 × 1050; initially 62.9 lb) were used from 2 barns in a 55-d growth trial. On d 0 of the trial, pens of pigs were blocked by weight and randomly allotted to 1 of 6 dietary treatments with 27 pigs per pen and 14 pens per treatment (7 pens per barn). Treatments were fed in 2 different phases. Phase 1 diets were fed from d 0 to 29 (62.9 to 112.6 lb) and phase 2 diets were fed from d 29 to 55 (112.6 to 159.7 lb). Treatments consisted of a control with inorganic P from monocalcium P, or 5 diets with 1,500 phytase units (FYT/kg) (Ronozyme HiPhos 2,500; DSM Nutritional Products, Inc., Parsippany, NJ) assuming different supplier- provided nutrient release values (Ca and P; Ca, P, and AA; Ca, P, AA, and half of the suggested net energy (NE); Ca, P, AA, and full NE; or no nutrient release). The assumed release values were 0.146% STTD P, 0.166% available P, 0.102% STTD Ca, 19 kcal/lb of NE; and 0.0217, 0.0003, 0.00886, 0.0224, 0.0056, 0.0122, and 0.0163% digestible Lys, Met, Met + Cys, Thr, Trp, Ile, and Val, respectively. All diets within phase were corn-soybean meal-based and contained a standardized total tract digestibility (STTD) Ca:STTD P ratio of 1.60:1 with all amino acids (AA) set to meet or exceed NRC requirement estimates. Overall (d 0 to 55), there was no evidence for difference in average daily gain (ADG) or average daily feed intake (ADFI). However, pigs fed the diet containing 1,500 FYT/kg assuming no nutrient release had improved (P<0.05) feed efficiency (F/G) compared to pigs fed diets containing 1,500 FYT/kg assuming either Ca and P or Ca, P, AA, and full NE release, with others intermediate. In the economic analysis, there was no evidence for difference (P>0.10) in feed cost per pig or feed cost per lb gain. In conclusion, based on diet formulation, pigs fed either the control diet with inorganic P from monocalcium P or any of the phytase-containing diets should have had similar performance, with the exception of pigs fed the diet formulated to contain 1,500 FYT/kg assuming no release values. However, pigs fed full matrix release values had the poorest (P<0.05) F/G, while pigs fed diets assuming Ca and P in addition to AA and half NE had F/G comparable to the control. This suggests the full matrix release values, especially energy, attributed to the phytase may be too aggressive and resulted in diets contributing fewer nutrients than needed to optimize performance.
Keywords: growing pig; phytase; release value